Grain storage in polymer sleeves as an answer to the challenge of the wartime in Ukraine - Barabolia, O. (Scientific Progress & Innovations, 2024)
The impact of military operations on agricultural production is catastrophic and is manifested in decreasing the areas of farmlands because of occupation or mining, the lack of labor force, rising prices of resources (seeds, fertilizers, fuel) at simultaneous decreasing the cost of manufactured products as a result of the complicated marketing logistics, destroying and damaging granaries and machinery. The purpose of the article is to study the peculiarities of using polymer sleeves for grain storage under hostilities on the territory of Ukraine. In similar conditions, the question arises of using non-traditional technologies of grain storage, the so called Argentine technology of grain storage in polymer sleeves can be referred to them. At present, it is the best of all known technologies of moist grain storage not only for fodder, but also for food purposes, and the cost of storage is approximately by 2–3 times lower, than on an elevator. Owing to high sleeve hermetic properties, grain mass self-compaction takes place because of decreasing its biological activity, and grain storage under zero temperatures assists in the natural cooling the sleeve content. The expediency of using grain sleeves is also stipulated by logistic peculiarities that are connected with the seasonal fluctuations of grain production. It has been proven by the investigations that the storage in polymer sleeves without losing grain amount and quality is possible for more than half a year depending on its moisture content. At present, the method of the controlled atmosphere is used to improve the process of storage; this method presupposes the creation of atmospheric gases mixture rich in CO2 and a low content of O2, or their combination. The use of special wireless sensors of Internet-of-Crops® platform produced by Centaur company, is also introduced for the remote monitoring the temperature, grain humidity, O2 and/or CO2 concentration, which enables to control grain quality when it is stored in any granary.